Association between genetic polymorphisms of SLCO1B1 and susceptibility to methimazole‐induced liver injury. Issue 6 (15th July 2019) - Jin, Shasha; Li, Xuesong; Fan, Yujuan; Fan, Xiaofang; Dai, Yu; Lin, Haishu; Cai, Weimin; Yang, Jialin; Xiang, Xiaoqiang
Abstract: Methimazole (MMI) has been used in the therapy of Grave's disease (GD) since 1954, and drug‐induced liver injury (DILI) is one of the most deleterious side effects. Genetic polymorphisms of drug‐metabolizing enzymes and drug transporters have been associated with drug‐induced hepatotoxicity in many cases. The aim of this study was to investigate genetic susceptibility of the drug‐metabolizing enzymes and drug transporters to the MMI‐DILI. A total of 44 GD patients with MMI‐DILI and 118 GD patients without MMI‐DILI development were included in the study. Thirty‐three single nucleotide polymorphisms (SNPs) in twenty candidate genes were genotyped. We found that rs12422149 of SLCO2B1, rs2032582_AT of ABCB1, rs2306283 of SLCO1B1 and rs4148323 of UGT1A1 exhibited a significant association with MMI‐DILI; however, no significant difference existed after Bonferroni correction. Haplotype analysis showed that the frequency of SLCO1B1*1a (388A521T) was significantly higher in MMI‐DILI cases than that in the control group (OR = 2.21, 95% CI = 1.11‐4.39, P  = 0.023), while the frequency of SLCO1B1*1b (388G521T) was significantly higher in the control group (OR = 0.52, 95% CI = 0.29‐0.93, P  = 0.028). These results suggested that genetic polymorphisms of SLCO1B1 were associated with susceptibility to MMI‐DILI. The genetic polymorphism of SLCO1B1 may be important predisposing factors for MMI‐induced hepatotoxicity.